Corporate Governance, Environmental Responsibility and Firm Value: An Empirical Study in Indonesia and Malaysia - Rintan Nuzul Ainy; Zuni Barokah (Journal of Accounting and Investment, 2019)
This study examines the correlation between corporate governance, environmental responsibility, and firm value in Indonesia and Malaysia. This study extends the literature in consideration of the role of environmental responsibility in indirect correlation between corporate governance and firm value. The environmental responsibility data index is calculated by conducting a content analysis of companies’ annual and sustainability reports in 2013. The other data are obtained from the database of OSIRIS, Bursa Malaysia (Stock Exchange of Malaysia), and Bursa Efek Indonesia (Indonesia Stock Exchange). The results show that corporate governance influences the company’s decision in performing voluntary activities such as environmental responsibility. This study shows that Malaysian and Indonesian markets do not respond to environmental responsibility information. It may be considered that the public in Malaysia and Indonesia lacks awareness of the importance of environmental responsibility.